Three mosques associated with the battle of Uhud: their importance, history and architecture - Spahic, Omer (IIUM Press, 2023)
This article discusses the importance, history and architecture of three mosques associated with the Uhud battle. The mosques are: masjid al-Fash, masjid al-Dir‘ and masjid al-Mustarah. These mosques are of a number of thronged landmarks found at or near the Uhud battlefield. The article concludes that the three mosques, though historically and to some extent architecturally remarkable, do not contain any corresponding religious significance. They are mere historical buildings commemorating certain, however critical, historical events and their sites. Thus, the mosques are not to be promoted from the level of historicity to that of religiosity, and are to be neither spiritualized nor ritualized. The mosques convey a number of lessons in the history of the nascent Madinah society, as well as in the nature of the development of Islamic culture and civilization. The research method adopted is interdisciplinary in character; it is a blend of descriptive, analytical and historical methods. A variety of sources, both primary and secondary, have been used. A field visit to the three mosques has also been performed.